Pengaruh Produk Domestik Regional Bruto Dan Tingkat Pengangguran Terbuka Terhadap Indeks Pembangunan Penduduk Provinsi Lampung (2013-2023) - Reychel Clara Adinda; Siti Khusnul Khotimah; Winda Pitaloka; Muhammad Kurniawan (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Economic growth is the key to successful development and increased prosperity in developing countries like Indonesia. This study uses secondary data from 2013-2023 to analyze the influence of the Human Development Index, Unemployment Rate and GRDP on development. The results show that GRDP and Unemployment Rate do not have a significant effect on the Human Development Index. Therefore, it is important for the authorities to facilitate job seekers in finding work, even if they do not work in Lampung Province.